A Quasi-Experimental Study on the Effectiveness of Compulsory and Voluntary Treatment Settings for 1,299 Drug Abusers in Hunan, China - Huang, Kai; Yu, Caihua; Chen, Xinxin; Hao, Yuzhu; Ding, Yudan; Wu, Zhenzhen; Wang, Xuyi (Frontiers in Psychiatry, 2021)
Background: Although the type and structure of substance abuse treatment have changed, the overall approaches of drug rehabilitation in China has remained largely unchanged. Evidence of effectiveness for compulsory drug rehabilitation centers (CRCs) and voluntary drug rehabilitation centers (VRCs) remains mixed. The main objective of our study is to reveal the outcomes of CRCs and VRCs and examine the factors associated with relapse in these two centers. Methods: In this cross-sectional study, we recruited a total of 1,299 drug abusers in Hunan Province, 709 from CRCs and 590 from VRC, respectively. We used Pearson chi-squared test and T-test to examine the differences in demographics and drug-related characteristics. Binary logic regression was used to examine the relationship between important factors and relapse in CRCs and VRC. Results: Patients from CRCs and VRC significantly differed in age, sex, types of drug used, medical illness, education, occupation, mental illness and marital status. After drug rehabilitation, both groups both had improved in occupation, family support and social function (p<0.05). In addition, employment and family support were significantly associated with a decreased risk of relapse (p<0.05). Conclusion: This study revealed that compulsory rehabilitation is as effective as voluntary rehabilitation in 1) getting jobs and increasing monthly income, 2) having a good relationship with family, and 3) becoming more satisfied with their spared time. The components of these two settings were very different and may imply the necessity of these two approaches in China. In addition, employment and family support may prevent relapse.